Chemical spectral shift control method for VVER-1000 LEU fuel assembly benchmark. (January 2022) - Elzayat, T.; Chertkov, Y.B.; Ashraf, O.
Highlights: The reactivity control was accomplished by varying the ratio of D 2 O / H 2 O . The chemical SSC method was applied to analyze the VVER-1000 LEU fuel assembly. The chemical SSC method was compared to the conventional poison method. The discharge burnup was improved by 60%. Abstract: The spectral shift control (SSC) is a promising method to decrease the fuel cycle cost and enhance the utilization of fuel resources (U, Pu) in nuclear reactors. In the chemical SSC method, reactivity control is accomplished by varying the ratio of heavy water to light water moderator (D2 O/H2 O). In the current work, we apply the chemical SSC method to analyze the VVER-1000 LEU fuel assembly from the OECD benchmark. Additionally, we compare the chemical SSC method to the conventional poison method presented in the benchmark. The results showed that the discharge burnup was improved by 60% and the conversion ratio value reached 0.83. The k∞ was suppressed at the beginning of cycle by −8% compared to the benchmark model. Furthermore, the dedication of 12 burnable absorber rods with 4.0 wt% Gd2 O3 would save the D2 O quantity during the adjustment process resulting in reducing the capital cost of the SSC method. However, it's found that the physical changes associated with applying the SSC method including a high contribution of 239 Pu and 241 Pu to power generation, the low effect of 135 Xe and 149 Sm on the reactivity system, and reduction of control rod worth should be considered in the safety analysis of the SSC design.